Simulating a multi-level priority triage system for Maternity Emergency - Abelha, António (2014)
Nowadays Decision Support Systems are increasingly used in order to help health professionals. An example of this application is the implementation of a triage system in hospital emergency. These systems allow more effective and rapid decisions taking into account the clinical needs of patients. In Centro Materno Infantil do Norte it was implemented an intelligent system of pre-triage which aims to prioritize the patients on two levels: Urgent (URG) and (ARGO). However, although specific for obstetrics and gynecology cases, the system does not meet all clinical requirements. Thus using a simulation algorithm developed within this framework, it was intended to simulate a specific priority triage system for gynecology and obstetrics but with five levels of acuity as suggested by the Portuguese general department of Health (Direção Geral de Saúde). For this study the repository of specific pre-triage system was used to test the algorithm. After application, it was found that the implementation of this system in Centro Materno Infantil do Norte will reduce waiting time, allowing a uniform distribution according to the waiting time and the clinical features. The percentage of deviation between the waiting time and the actual time obtained by simulation algorithm is approximately 121.6%